Pengembangan: Indeks Pembangunan Islam - Acha, Hurul Aini (Scimadly Publishing, 2024)
The purpose of this study is to compare the world's nations according to their level of development from an Islamic perspective and to assess the best metrics for development from an Islamic perspective. This research is descriptive-quantitative and is based on two methodologies at the same time: conceptual, which utilizes qualitative methods, and empirical, which uses quantitative methods. In particular, the top five scores of Qatar, Kuwait, Indonesia, Tunisia, and Turkey are rated first, second, third, and fifth, respectively, according to the analysis, which shows the ranking Islamic Development Index (IDI) for the highest score group. The Middle Eastern nation that ranks highest on the IDI list is Qatar. This nation is among those with the greatest per capita incomes in the world. Among Arab nations, Qatar is ranked as having the best and highest human development index. The protection of religion, the protection of the soul, the protection of the intellect, the protection of children, and the protection of property/wealth are some indications that can help the five nations with the highest scores achieve the goals of Maqasid Syari'ah. The majority of MENA nations, including Morocco, Jordan, Lebanon, Yemen, and Libya, continue to control the low-scoring IDI groupings.